Effect of element evaporation on the microstructure and properties of CuZnAl shape memory alloys prepared by selective laser melting. (July 2020) - Zhuo, Linrong; Song, Bo; Li, Ruidi; Wei, Qingsong; Yan, Chunze; Shi, Yusheng
Highlights: The interrelationships among process parameters, microstructure and macroscopic properties are established. Effect of element evaporation on microstructure and transformation behavior is presented. Effect of the thermal effect during SLM process on martensite formation is revealed. Abstract: Cu-based shape memory alloys are promising materials for functional or intelligent applications because of its good shape memory properties and low cost. As an additive manufacturing technique, selective laser melting (SLM) is easy to produce such complex intelligent components, moreover, the rapid solidification rate can obtain fine microstructure and get good properties. In this study, CuZnAl shape memory alloys were prepared by SLM for the first time to study the effect of the process parameters on the relative density, phase constitution, microstructure, phase transformation behavior, microhardness and superelastic response. Results show that the intrinsic reason for the differences in the microstructure and the macroscopic properties is the different Zn content in samples fabricated with different energy densities. The lower energy densities lead to the lower amount of Zn evaporation and thus the higher remained Zn content in the fabricated samples. In terms of phase constitution, samples with higher Zn content mainly consist of martensite (β') and present needle-like shape microstructure morphology. On the contrary, samples with lower Zn content are predominated by α phase and have rod-like or even equiaxed shape microstructure. In addition, higher amount of martensite in the samples results in the higher peak intensity in the DSC curves, the higher microhardness and the lower irrecoverable strain.